Identification and validation of novel microtubule suppressors with an imidazopyridine scaffold through structure-based virtual screening and docking. Issue 8 (30th May 2022) - Elseginy, Samia A.; Oliveira, A. Sofia F.; Shoemark, Deborah K.; Sessions, Richard B.
Abstract : A fast and effective route to find compounds targeting mitosis. New compounds towards cancer therapeutics. Abstract : Targeting the colchicine binding site of α/β tubulin microtubules can lead to suppression of microtubule dynamics, cell cycle arrest and apoptosis. Therefore, the development of microtubule (MT) inhibitors is considered a promising route to anticancer agents. Our approach to identify novel scaffolds as MT inhibitors depends on a 3D-structure-based pharmacophore approach and docking using three programs MOE, Autodock and BUDE (Bristol University Docking Engine) to screen a library of virtual compounds. From this work we identified the compound 7-(3-hydroxy-4-methoxy-phenyl)-3-(3-trifluoromethyl-phenyl)-6, 7-dihydro-3 H -imidazo[4, 5-b]pyridin-5-ol (6 ) as a novel inhibitor scaffold. This compound inhibited several types of cancer cell proliferation at low micromolar concentrations with low toxicity. Compound 6 caused cell cycle arrest in the G2/M phase and blocked tubulin polymerization at low micromolar concentration (IC50 = 6.1 ±0.1 μM), inducing apoptosis via activation of caspase 9, increasing the level of the pro-apoptotic protein Bax and decreasing the level of the anti-apoptotic protein Bcl2. In summary, our approach identified a lead compound with potential antimitotic and antiproliferative activity.